Komparativna analiza imunološkog statusa fudbalera razlicitih nivoa takmicenja - Sekulic, Ž.; Dragosavljevic, S.; Budimlic, J.; Ilic, N. (Sports Science and Health, 2026)
The aim of this study was to examine the immune status of football players at different competition levels in Bosnia and Herzegovina through the analysis of key hematological biomarkers. The sample included 59 football players from the first, third, and fifth leagues, whose immune parameters were analyzed based on medical records and laboratory findings. The measured parameters included absolute counts of leukocytes, lymphocytes, monocytes, neutrophils, eosinophils, and basophils. The results did not show statistically significant differences between players from different leagues, although certain variations in individual biomarkers were observed. These findings suggest that the competition level itself is not a key factor in determining the immune responses of athletes under stable physiological conditions. It is concluded that further research is needed, covering different phases of the training cycle, to better understand the impact of training load and periodization on the immune status of football players.